STRATEGIC INTEGRATION AND VALUE CAPTURE: ENHANCING INDONESIA'S PARTICIPATION IN GLOBAL VALUE CHAINS (GVC) FOR SUSTAINABLE ECONOMIC GROWTH - Putra, Fajar Surya (Scientia Integritas Utama, 2023)
The rise of global value chains (GVCs) has redefined international trade, enabling countries to specialize in different stages of production. Indonesia’s participation in GVCs is crucial for enhancing industrial productivity and export diversification. However, Indonesia still heavily relies on forward participation, primarily exporting raw materials and commodities, which makes its economy vulnerable to global price fluctuations. This paper examines Indonesia’s trade characteristics, GVC participation trends, and the implications of both forward and backward participation for economic growth. The study highlights the need for strategic policies to balance these two forms of participation by fostering domestic industrial development, improving human capital, and investing in technology. Furthermore, the role of financial services and infrastructure is explored in facilitating backward participation, enabling Indonesia to integrate more effectively into the global production network. To optimize GVC benefits, Indonesia must adopt a multifaceted approach that includes economic diversification, technological advancement, and policy reforms. Strengthening collaboration with ASEAN countries and improving domestic capabilities will be critical in ensuring sustainable economic development and increasing global competitiveness.